Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.7861/futurehosp.6-1-56
|View full text |Cite
|
Sign up to set email alerts
|

Education and Training: Perceived educational impact, ­challenges and opportunities of hospice placements for foundation year doctors: a qualitative study

Abstract: Foundation year one doctors (F1s) are expected to recognise and care for dying patients, but previous studies have found they can feel unprepared, stressed and unsupported when faced with such situations. Although hospice placements can provide good experiential learning for junior doctors, no studies to date have included F1s. This study used an interpretivist approach to explore educational opportunities and challenges in hospice placements from an F1's perspective. Six F1s who had recently completed hospice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“… 17 There was one exception where junior doctors reported hospice placements as medically deskilling experiences, but this had a low weight of evidence. 20 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 17 There was one exception where junior doctors reported hospice placements as medically deskilling experiences, but this had a low weight of evidence. 20 …”
Section: Resultsmentioning
confidence: 99%
“…All the papers provided evidence that the majority of junior doctors provide palliative and end-of-life care for many patients early in their careers 11–49. An average of 40% (range: 36%–46%) of junior doctors cared for 1–10 patients, while 51% (range: 40%–61%) of junior doctors cared for more than 10 patients 16 26 38 44…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also found that clinical experience during clerkships has the greatest impact in improving student end-of-life care knowledge and competence [ 10 , 30 ]. Increased clinical exposure is positively correlated with increased confidence [ 31 , 32 ]. However, our respondents described isolated workshops that lacked strategy or cohesion and short-term rotations with limited clinical exposures to palliative patients.…”
Section: Discussionmentioning
confidence: 99%